Description of the Effectiveness of the Implementation Moodle Learning Management System-Based Online Learning - Zainuddin Sani; Muhammad Irham; Rizky Fadillah (Jurnal Equation: Teori dan Penelitian Pendidikan Matematika, 2023)
This study aims to describe how effective the implementation of online learning based on Moodle LMS in the mathematics education study program is with the type of mixed (method research). Quantitative data collection methods using questionnaires and qualitative methods using interviews. The subjects given the questionnaire consisted of all students and lecturers in the mathematics education study program. The subjects interviewed were selected using a purposive sampling consisting of 2 lecturers and 3 students with consideration of the types of courses taught for lecturers and semesters taken for students. Quantitative analysis technique uses descriptive percentage analysis and qualitative data analysis technique uses data reduction, data presentation, and conclusion stages. The results showed that, (1) the implementation of moodle LMS-based online learning in the student's perspective was in the quite effective category with a percentage of 79.78%, (2) the implementation of moodle LMS-based online learning in the lecturer's perspective was also in the quite effective category with a percentage of 66 ,66%.